2015
DOI: 10.1039/c5ra02174j
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive 18(4 → 3)-abeo-abietanoid derivatives from the leaves of Tripterygium wilfordii

Abstract: Tripterlides A–F are new abietane derivatives, obtained from Tripterygium wilfordii. 1–4 are novel 14(13 → 12),18(4 → 3)-diabeo-abietanoids possessing a 6/6/5 tricyclic ring system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…Tripordolide B ( 2 ) was obtained as a colorless oil and showed a [M + Na] + ion peak at m/z 399.1052 (calculated for 399.1050) in the HRESIMS, which corresponded to the molecular formula C 19 H 20 O 8 . Some obvious signals, a ring of α, β-unsaturated-γ-lactone [ δ H 5.42 (2H, m, H-17); δ C 170.4 (C-18), 68.9 (C-19), 124.4 (C-3), and 146.5 (C-4)] and an oxygen isopropyl group [ δ H 1.23, 1.41 (each 3H, s, H 3 -16 and H 3 -17); δ C 25.2(C-16), 26.8 (C-17), and 73.6 (C-15)], indicated 2 was also an 18(4→3)-abeo-abietane derivative ( Table 1 ) and similar to a less 20-CH 3 and aromatized nor-abietane, tripterlide F [ 16 ]., This was proven by the HMBC correlations of H-1 [ δ H 7.22 (1H, d, J = 8.0 Hz)]/C-4, C-5 ( δ C 128.7) and C-9 ( δ C 60.7); of H-2 [ δ H 7.70 (1H, d, J = 8.0 Hz)]/C-4, C-10 ( δ C 138.5) and C-18 ( Figure 2 ). Some major differences between the two compounds in the chemical shift values of C-12 and C-13 were observed, which could be attributed to the breakage of a trisubstituted epoxide between C-12 ( δ C 69.7) and C-13 ( δ C 74.9).…”
Section: Resultsmentioning
confidence: 99%
“…Tripordolide B ( 2 ) was obtained as a colorless oil and showed a [M + Na] + ion peak at m/z 399.1052 (calculated for 399.1050) in the HRESIMS, which corresponded to the molecular formula C 19 H 20 O 8 . Some obvious signals, a ring of α, β-unsaturated-γ-lactone [ δ H 5.42 (2H, m, H-17); δ C 170.4 (C-18), 68.9 (C-19), 124.4 (C-3), and 146.5 (C-4)] and an oxygen isopropyl group [ δ H 1.23, 1.41 (each 3H, s, H 3 -16 and H 3 -17); δ C 25.2(C-16), 26.8 (C-17), and 73.6 (C-15)], indicated 2 was also an 18(4→3)-abeo-abietane derivative ( Table 1 ) and similar to a less 20-CH 3 and aromatized nor-abietane, tripterlide F [ 16 ]., This was proven by the HMBC correlations of H-1 [ δ H 7.22 (1H, d, J = 8.0 Hz)]/C-4, C-5 ( δ C 128.7) and C-9 ( δ C 60.7); of H-2 [ δ H 7.70 (1H, d, J = 8.0 Hz)]/C-4, C-10 ( δ C 138.5) and C-18 ( Figure 2 ). Some major differences between the two compounds in the chemical shift values of C-12 and C-13 were observed, which could be attributed to the breakage of a trisubstituted epoxide between C-12 ( δ C 69.7) and C-13 ( δ C 74.9).…”
Section: Resultsmentioning
confidence: 99%
“…Sugar moieties were confirmed to be d -glucose and l -rhamnose by silylation followed with gas chromatography (GC) analysis. The absolute configuration of 1a was defined as 8S by comparison of the experimental ECD spectra and the calculated ECD data using the time-dependent density functional theory (TDDFT) method at the B 3 LYP/6-31G (d) level [ 13 ]. The calculated ECD spectrum of (8S) 1a ( Figure 3 ) matched the experimental spectrum of 1a and 1 very well, which indicated that the structure of 1a had not changed in the process of acid hydrolysis and the absolute configuration of 1 was elucidated as 8S.…”
Section: Resultsmentioning
confidence: 99%
“…The leaves of Tripterygium wilfordii (Taining, Fujian, China) contained six new abietane diterpenoids, tripterlides A–F. Tripterlides E ( 284 ) and F ( 285 ) displayed potent cytotoxicities against HCT-116, HepG2, BGC-823, and H460 cells with IC 50 ranges of 0.93–3.16 and 0.17–0.90 μM, respectively (Wang et al, 2015a ). Six new cardenolide glycosides were discovered from the roots of Streptocaulon juventas (Yunnan, China).…”
Section: Terrestrial Plantsmentioning
confidence: 99%